PEMODELAN PROSES BISNIS MENGGUNAKAN BPMN USAHA KAROSERI MODIFIKASI AMBULANS STUDI KASUS BAMBTEK - Theodora, Marry Caroline; Rudianto, Christ (JURNAL LENTERA BISNIS, 2026)
This study aims to model the business processes of Bambtek, an ambulance modification coachbuilding business, using the Business Process Model and Notation (BPMN) approach. The main problem faced by Bambtek is the absence of structured business process documentation, causing several operational activities to rely on the owner’s experience, which may lead to overlapping roles and potential miscommunication in business operations. This research employs a qualitative method through interviews, observations, and literature studies to collect relevant data. The results indicate that BPMN modeling can represent the business process flow systematically, covering marketing and sales, vehicle unit procurement, functional testing, and warranty services. Furthermore, the study provides recommendations for improving business processes to enhance operational efficiency, clarify task distribution, and support decision-making as well as the future development of Bambtek.